Oleoresin Yield and Gum Rosin Properties from Sulawesi and Sumedang Sub-lines of Pinus merkusii Wood - Sheany Citra Sukma Wijaya; Sigit Sunarta; Suryo Hardiwinoto; Wdiyatno Widiyatno; Ganis Lukmandaru; Daryono Prehaten (Wood Research Journal, 2025)
Progeny testing can be performed to reach high oleoresin production from Pinus merkusii. This study aimed to determine and compare the oleoresin yields and rosin properties of 15-year-old Pinus merkusii wood of the Sumedang and Sulawesi sub lines from the KPH Banyumas Barat plantation. Tree diameter and oleoresin yield were observed in 20 individual trees of each sub-line. Tree tappings were conducted by the drilling method for three days, which was replicated for five times over a 15-day observation period. Gum rosin samples were obtained from all trees by the hydro-distillation method. The results showed that the tree diameters at breast height and oleoresin yields of the Sumedang sub-line fell in the ranges 22.0–34.2 cm and 10.8 51.2 g/tree/3 days, respectively, whereas those of the Sulawesi sub-line fell within the ranges 19.4–31.2 cm and 11.6–50.4 g/tree/3 days, respectively. Based on t-test results, no significant difference was found between the two sub-lines. The gum rosin yields were 52–79% and 55–78% for the Sumedang and Sulawesi sub-lines, respectively. With regard to rosin properties, the softening point, acid number, saponification value, toluene-insoluble content, and volatile content were 77.80 ± 4.08°C, 189.51 ± 10.51, 216.54 ± 10.51, 0.08 ± 0.11%, and 3.78 ± 3.56%, respectively, for the Sumedang sub-line and 66.35 ± 6.55°C, 78.15 ± 2.92, 189.86 ± 10.68, 208.02 ± 10.50, 0.06 ± 0.11%, and 9.82 ± 2.95%, respectively, for the Sulawesi sub-line. Significant effects of sub-line were only observed in terms of saponification value and volatile content, where the rosin from the Sumedang sub-line had better properties than the rosin from the Sulawesi sub-line. These differences indicate different compositions of chemical components of oleoresin or rosin between sub-lines.